A percepção de vogais do português brasileiro por falantes nativos do inglês americano - Chaves, Patricia Xavier (2024)
The project aimed at developing oral skills in L2 is challenging, as both from the point of view of sound discrimination and their production, L1 interference occurs. This research aims to develop a study on the perception of vowel sounds in Brazilian Portuguese (as L2) by native speakers of American English. We used the Speech Learning Model (Flege, 2005), as a theoretical foundation, which defends the need for L2 learners to create perceptual targets so that new categories of sounds are acquired. Every language has an inventory of its own phonemes. When acquiring a new language, L1 interference prevents the perception of sounds that are discriminated in the L2 and not in the L1, which causes interference in the quality of sound production by L1 speakers. Vowel sounds were chosen for analysis purposes, as English and Portuguese have a diverse number of phonemes and some contrasts found in English are not found in Portuguese. In the Brazilian Portuguese language there are 7 oral vowel phonemes and in the English language there are 11. The research participants are native speakers of Brazilian Portuguese who will perform the speech production task and native speakers of American English who will perform the perception task. As a research question we have: Which pairs of vowel sounds in Portuguese are assimilated to just one sound in American English? How does the phonemic inventory of the English language as L1 affect the processes of assimilation of vowel sounds discriminated in L2, and prevent the formation of new categories? The hypothesis is that Americans will not be able to perceive some pairs of sounds in Portuguese, since the phonemic inventories of the two languages are different. The particularity of the project is because there is little research into Brazilian Portuguese spoken by native speakers of American English